The Validation of Chromatographic Methods in the Detection of Cocaine and Diluents in Drugs Seized by the Civil Police in the State of Espírito Santo - Miossi, Karoline P.; Valin, Thays C.; Bottocim, Ramon R. T.; Araújo, Bruno Q.; Romão , Wanderson; de Castro, Eustaquio V. R.; Lacerda Jr., Valdemar; Cunha Neto, Alvaro (Orbital: The Electronic Journal of Chemistry, 2025)
Over the years, police have seized tons of cocaine in the form of cocaine hydrochloride and crack, which are often adulterated by traffickers. This work aims to use GC/MS and HPLC to determine the limit of detection (LoD) and limit of quantification (LoQ) of 10 seized samples of crack and 10 of cocaine hydrochloride. All samples were provided by the Civil Police of Espírito Santo State (CP/ES) and each sample was analyzed in triplicate using GC/MS and HPLC-DAD. For the first technique, a correlation coefficient (R) equals 0.9939 was achieved, while for HPLC a R = 0.9984 was obtained for crack and R = 0.9907 for cocaine. Due to the validated methods, it was possible to determine the LoD and LoQ for the cocaine present in the samples, in addition to identifying some diluents, such as caffeine and phenacetin.